Are the Objectives Proposed by the WHO for Routine Measles Vaccination Coverage and Population Measles Immunity Sufficient to Achieve Measles Elimination from Europe? - Plans-Rubió, Pedro (Vaccines (Basel), 2020)
Background: The World Health Organization (WHO) proposed two-dose measles vaccination coverage of at least 95% of the population and percentages of measles immunity in the population of 85%−95% in order to achieve measles elimination in Europe. The objectives of this study were: (1) to determine the measles vaccination coverage required to establish herd immunity against measles viruses with basic reproduction numbers (Ro) ranging from 6 to 60, and (2) to assess whether the objectives proposed by the WHO are sufficient to establish herd immunity against measles viruses. Methods: The herd immunity effects of the recommended objectives were assessed by considering the prevalence of protected individuals required to establish herd immunity against measles viruses with Ro values ranging from 6 to 60. Results: The study found that percentages of two-dose measles vaccination coverage from 88% to 100% could establish herd immunity against measles viruses with Ro from 6 to 19, assuming 95% measles vaccination effectiveness. The study found that the objective of 95% for two-dose measles vaccination coverage proposed by the WHO would not be sufficient to establish herd immunity against measles viruses with Ro ≥ 10, assuming 95% measles vaccination effectiveness. By contrast, a 97% measles vaccination coverage objective was sufficient to establish herd immunity against measles viruses, with Ro values from 6 to 13. Measles immunity levels recommended in individuals aged 1−4 years (≥85%) and 5−9 years (≥90%) might not be sufficient to establish herd immunity against most measles viruses, while those recommended in individuals aged 10 or more years (≥95%) could be sufficient to establish herd immunity against measles viruses with Ro values from 6 to 20. Conclusion: To meet the goal of measles elimination in Europe, it is necessary to achieve percentages of two-dose measles vaccination coverage of at least 97%, and measles immunity levels in children aged 1−9 years of at least 95%.